Roles of catecholamines and inflammation in endothelial dysfunction: a study using Takotsubo syndrome patient-specific hiPSC-ECs - Yang, Guoqiang; Zhong, Luyi; Wang, Jiayue; Yang, Chenyu; Cyganek, Lukas; Hamdani, Nazha; Zhou, Xiao-Bo; Fan, Xuehui; El-Battrawy, Ibrahim; Akın, Ibrahim (Stem cell reviews and reports, 2026)
Takotsubo syndrome (TTS), also known as stress-induced cardiomyopathy, is characterized by transient left ventricular dysfunction often triggered by emotional or physical stress. Catecholamines are believed to play a pivotal role in the pathogenesis of TTS, including endothelial dysfunction. This study aimed to elucidate the catecholamine-induced endothelial dysfunction using patient-specific induced pluripotent stem cell-derived endothelial cells (hiPSC-ECs) from TTS patients.
Gesehen am 26.02.2026